Treatment of Pusher Syndrome in a patient after extensive cerebral infarction caused by cerebral embolism - case report - Piotr Porzych; Dorota Ratuszek-Sadowska; Małgorzata Pyskir; Krystyna Nowacka; Joanna Simińska; Anna Lewandowska; Maciej Dzierżanowski; Magdalena Hagner-Derengowska (Kazimierz Wielki University, 2017)
Pusher Syndrome is defined as a disorder of perception of body orientation in the frontal plane. It is mainly observed in patients after stroke in consequence to damage to the right or left hemisphere of the brain. Characteristic clinical symptoms in people affected by this syndrome are leaning towards the paralyzed side of the body and building massive resistance during passive correction. The consequence of such behavior are falls in the direction of the affected side. The paper presents the case of a patient who, after extensive right hemisphere cerebral hemorrhage, was admitted to the Chair and Department of Rehabilitation Medicine of the Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz to improve. During treatment the patient was used the neurorehabilitation based on the Bobath concept.